2012
DOI: 10.2500/ajra.2012.26.3759
|View full text |Cite
|
Sign up to set email alerts
|

Central presentation of postviral olfactory loss evaluated by positron emission tomography scan: A pilot study

Abstract: Background Postviral olfactory loss after upper respiratory tract infection (URI) is not uncommon. However, its exact location and nature are not fully understood. Although it is likely to be caused by a direct damage of olfactory epithelium, a damage of the central pathway has also been suspected as its possible mechanism. This study will show basal metabolism in the brain of patients with postviral olfactory loss using fluorodeoxyglucose-positron emission tomography (FDG PET). Methods Nine patients with po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 22 publications
(30 reference statements)
1
27
0
Order By: Relevance
“…For example, in patients with POL, the main suspected mechanism is a damage of olfactory epithelium: we know that MRI of the olfactory bulb show a reduction of its volume ( Rombaux et al, 2006 ) and biopsy of the olfactory cleft reveal a diminution of the olfactory receptors ( Yamagishi et al, 1994 ). However, central damage during viral infection are also suspected ( Kim et al, 2012 ). Different kind of viruses can induce a POL, including coronaviruses ( Chen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in patients with POL, the main suspected mechanism is a damage of olfactory epithelium: we know that MRI of the olfactory bulb show a reduction of its volume ( Rombaux et al, 2006 ) and biopsy of the olfactory cleft reveal a diminution of the olfactory receptors ( Yamagishi et al, 1994 ). However, central damage during viral infection are also suspected ( Kim et al, 2012 ). Different kind of viruses can induce a POL, including coronaviruses ( Chen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…These notions led to suspect another pathogenesis than a nasal obstruction for anosmia, as it is described in post-viral olfactory loss (POL) which can also be associated with dysgeusia [15]. The pathogenesis of POL involves probably a damage of the sensory receptors [16] or a lesion of the neural system (olfactory cranial nerve or central lesion) [17].…”
Section: Clinical Description Of Patients With Covid-19mentioning
confidence: 99%
“…Furthermore, 70% of patients who reported complete resolution proved hyposmic to an objective test. Also, the study population subgroup analysis showed a high frequency of olfactory disorders throughout the observation period, ranging between 77.4% (days 1-4) and 69.2% (days [25][26][27][28][29][30][31][32][33][34][35]. Anosmia or severe hyposmia affected 70.9% of patients in the early stages; they improved after the first 10 days, reaching moderate hyposmia values.…”
Section: Epidemiologymentioning
confidence: 85%
“…On the contrary, Kim and Hong demonstrated that persistent PVOD is associated with decreased metabolism in specific brain regions where the olfactory stimuli are processed and integrated, suggesting that anosmia is, in some cases, caused by a central injury mechanism (25). Virally induced damage of OB and other brain areas was highlighted through magnetic resonance imaging correlating olfactory function with OB volume (26).…”
Section: Physiopathologymentioning
confidence: 99%